2010
DOI: 10.1074/jbc.m109.089805
|View full text |Cite
|
Sign up to set email alerts
|

N-type Calcium Channel in the Pathogenesis of Experimental Autoimmune Encephalomyelitis*

Abstract: One of the family of voltage-gated calcium channels (VGCC), the N-type Ca 2؉ channel, is located predominantly in neurons and is associated with a variety of neuronal responses, including neurodegeneration. A precise mechanism for how the N-type Ca 2؉ channel plays a role in neurodegenerative disease, however, is unknown. In this study, we immunized N-type Ca . These results suggest that the N-type Ca 2؉ channel is involved in the pathogenesis of EAE at least in part by regulating MCP-1 production by microglia. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Recent studies have shown that the inhibition of N-type voltage-gated calcium channels reduced the severity of EAE neurological symptoms and decreased demyelination and infiltration areas [50,51]. The authors indicated microglia/macrophages as the principal effectors of this improvement, demonstrating that inhibition of these voltage-gated calcium channels regulates microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the inhibition of N-type voltage-gated calcium channels reduced the severity of EAE neurological symptoms and decreased demyelination and infiltration areas [50,51]. The authors indicated microglia/macrophages as the principal effectors of this improvement, demonstrating that inhibition of these voltage-gated calcium channels regulates microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…Tokuhara and coworkers compared the clinical and pathological evolution of EAE in knockout mice for N-type channel pore forming subunit Ca V 2.2 (α 1B ) and in their wild type littermates [239]. As expected, the neurological symptoms and the spinal cord lesions were less severe in knockout than in wild type mice [239]. Also perilesional inflammation was less severe in knockout mice.…”
Section: Introductionmentioning
confidence: 96%
“…Also, the N-type channel blocker ω-conotoxin GVIA protects Norway rats from EAE-induced optic neuritis [238]. Tokuhara and coworkers compared the clinical and pathological evolution of EAE in knockout mice for N-type channel pore forming subunit Ca V 2.2 (α 1B ) and in their wild type littermates [239]. As expected, the neurological symptoms and the spinal cord lesions were less severe in knockout than in wild type mice [239].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of MS has often been studied using an animal model, EAE, that resembles the pathology of human MS (2). It is thought to be mediated in part by myelin-specific lymphocytes, and it shows infiltration of activated peripheral inflammatory cells into the CNS, attack of myelin by the immune system or cell death of oligodendrocytes, and axonal damage (3)(4)(5). Hence, to better understand the mechanism of the signs of EAE, EAE is characterized into two phases, an immune-mediated process and a neurodegenerative process (1).…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%